2018
DOI: 10.1002/dac.3540
|View full text |Cite
|
Sign up to set email alerts
|

An extended ECC‐based anonymity‐preserving 3‐factor remote authentication scheme usable in TMIS

Abstract: A telecare medicine information system (TMIS) helps in providing an efficient communication platform to patients from home to consult doctors at a clinical center. In TMIS, the patient's confidentiality, security, and mutual authentication are very crucial; so remote authentication plays a vital role for verifying the legitimacy of patients. Recently, Amin and Biswas have devised a remote authentication protocol for TMIS, claiming it to be secured from various malicious vulnerabilities. We examine this protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Also, the algorithms such 1024-bit Rivest-Shamir-Adleman (RSA) algorithm, 320-bits elliptic-curve (EC) cryptosystem, 128-bit advanced-encryption standard (AES), and 160 -bit secure-hash algorithm 1 (SHA-1) were employed to experiment the given assumption time that is as follows: ET H ≈ 0.0004 ms, ET SED ≈ 0.1303 ms, ET DM ≈ 1.8269 ms and ET ME ≈ 1.6003 ms in the given order [8]. From Table 3, the estimated execution time of the proposed S-USI scheme and other related schemes such as Nikooghadam et al [64], Chaudhry et al [65], Arshad et al [66], Lu et al [67], Amin and Biswas [69], and Chandrakar et al [75] were carefully examined to determine the execution time. The result of the proposed S-USI was 0.0689 ms, whereas the other related schemes were 0.0649 s, 0.5832 s, 0.3869 s, 0.2593 s, 0.3474 s, and 0.7689 s respectively.…”
Section: Comparison Of Communication and Storage Costmentioning
confidence: 90%
See 2 more Smart Citations
“…Also, the algorithms such 1024-bit Rivest-Shamir-Adleman (RSA) algorithm, 320-bits elliptic-curve (EC) cryptosystem, 128-bit advanced-encryption standard (AES), and 160 -bit secure-hash algorithm 1 (SHA-1) were employed to experiment the given assumption time that is as follows: ET H ≈ 0.0004 ms, ET SED ≈ 0.1303 ms, ET DM ≈ 1.8269 ms and ET ME ≈ 1.6003 ms in the given order [8]. From Table 3, the estimated execution time of the proposed S-USI scheme and other related schemes such as Nikooghadam et al [64], Chaudhry et al [65], Arshad et al [66], Lu et al [67], Amin and Biswas [69], and Chandrakar et al [75] were carefully examined to determine the execution time. The result of the proposed S-USI was 0.0689 ms, whereas the other related schemes were 0.0649 s, 0.5832 s, 0.3869 s, 0.2593 s, 0.3474 s, and 0.7689 s respectively.…”
Section: Comparison Of Communication and Storage Costmentioning
confidence: 90%
“…Assume that length of the identity of U sr U id and password P wd , random-integer and hash-function are set to 160 bits, whereas the elliptic-curve considers 320 bits and the symmetric key encryption/decryption carries a size of 512 bits [75]. In the S-USI scheme, three message rounds are considered such as M sg1 = ⟨P 1 , P 2 , TS 1 ⟩ , M sg2 = ⟨Q 1 , Q 2 , TS 2 ⟩ and ⟨R, H⟩ to transmit between U ser and R S .…”
Section: Comparison Of Communication and Storage Costmentioning
confidence: 99%
See 1 more Smart Citation
“… ROM‐based verification proof This formal security analysis verifies that an adversary may not be able to retrieve crucial secret parameters such as ID i , PW i , V 1 , and session key SK. We adopted the similar procedure to for this analysis as given in previous studies 23,36,37 . The random oracle is defined as follows:…”
Section: Security Analysismentioning
confidence: 99%
“…Still, the chebyshev chaotic maps are costly than symmetric hash‐based operations while the later has more compatibility for being inducted in the sensors ecosystem. Chandraker and Om 36 put forward another authentication scheme for TMIS‐based patient health care; however, it was vulnerable to offline‐password guessing and impersonation attack. Sharif et al 37 demonstrated an improved authentication scheme for WBAN; however, it is prone to session‐specific temporary information attack as well as key‐compromise impersonation attack.…”
Section: Introductionmentioning
confidence: 99%